Yen synchronization among ASEAN-5, Korea and Japan: evidence from the multivariate GARCH model - Wong, Kelly Kai Seng; Lee, Chin; Mohamed, Azali (Faculty of Economics and Management, Universiti Putra Malaysia, 2015)
In this study, we aim to investigate whether ASEAN-5 and the Korean currency regimes are ready to use Japanese Yen as an Asian future Exchange Rate Mechanism (AERM) by using Multivariate GARCH models. Overall findings show that Singapore, Thailand, and Korea are the potential countries that ready to adopt Japanese Yen as an AERM. However, Malaysian Ringgit, Indonesian Rupiah and the Philippines Peso are weakly correlated with Japanese Yen. This indicates that the East Asian free trade agreement such as ASEAN-10+3 and EAFTA does not enough to promote these low dynamic correlation countries (Malaysia, Indonesia, and the Philippines). Perhaps, the appropriate way to begin the AERM is to form a group of currency system which highly correlated with Japanese Yen (e.g. Singapore, Thailand, and Korea) whiles others could have a commitment to adopt Japanese Yen as a regional trade-invoicing currency in order to increase the level of Yen synchronization correlation.